Absorption study on the effect of mixed cation on tin and germanium-based perovskite solar cells. Issue 1 (November 2021) - William, M A; Azhari, A W; Hassan, N S B N; Hasan, N; Halin, D S C; Thottoli, A K
Abstract: The thin film industry has been introduced with an invention of lead-based perovskite solar cells which eventually has gained a huge attention throughout the years. As the concern arises, this lead-based perovskite solar cells contributed towards both the environmental and human health issues due to the high level of toxicity. This then carve the paths into the research in finding suitable alternative for lead-free perovskite where tin and germanium are proposed as possible substitute, but the long-term durability and stability of both perovskites are still a challenge to be improved and maintained. In this study, tin and germanium-based solutions are fabricated individually with mixed cations of FA-MA; FAx MA1–x SnI3 and FAx MA1–x GeI3 in variations (1⩽ x ⩽0). The UV-Vis spectroscopy was analyzed in 400-1100nm range to measure the light intensity absorption of full encapsulated fabricated perovskite solar cells after 30 days of exposure to surrounding conditions and recorded highest peak of absorption at the wavelength of 400 nm and 550 nm for tin based and germanium-based perovskite respectively.